Stroke from Vasospasm due to Marijuana Use: Can Cannabis Synergistically with Other Medications Trigger Cerebral Vasospasm?. (19th October 2016) - Jamil, Marium; Zafar, Atif; Adeel Faizi, Syed; Zawar, Ifrah
Abstract : We present a case of imaging proven cerebral vasospasm causing ischemic stroke in a young patient chronically on buprenorphine-naloxone for heroin remission who started smoking cannabis on a daily basis. With cannabis legalization spreading across the states in the USA, it is important for physicians not only to be aware of cannabis reported association with cerebral vasospasm in some patients but also to be on the lookout for possible interacting medications that can synergistically affect cerebral vessels causing debilitating strokes.